2021
DOI: 10.3390/w13050716
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prospective Climate Change Scenarios upon Hydropower Potential of Ethiopia in GERD and GIBE Dams

Abstract: Ethiopia is growing fast, and the country has a dire need of energy. To avoid environmental damages, however, Ethiopia is looking for green energy polices, including hydropower exploitation, with large water availability (i.e., the Blue Nile, the greatest tributary of Nile river). Besides other dams on the Omo river, the GIBE family, Ethiopia is now building the largest hydropower plant of Africa, the GERD (Grand Ethiopian Renaissance Dam), on the Blue Nile river, leading to tensions between Ethiopia, and Egyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A dry season guide curve and a rainy season guide curve are hydrological tools for managing water resources in places with distinct wet and dry seasons [ 34 ]. Based on historical data, these curves are used to calculate the quantity of water that may be released from a dam or reservoir during different seasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dry season guide curve and a rainy season guide curve are hydrological tools for managing water resources in places with distinct wet and dry seasons [ 34 ]. Based on historical data, these curves are used to calculate the quantity of water that may be released from a dam or reservoir during different seasons.…”
Section: Resultsmentioning
confidence: 99%
“…The planning and management of the water resources system include reservoir operation [ 34 ]. Three distinct sets of functions, referred to as modules, are provided by HEC-ResSim and give users access to various categories of data within a watershed.…”
Section: Methodsmentioning
confidence: 99%
“…This condition further justifies the value for an archaeological and ethnographic research to be undertaken, even if the dam is already in operation. If research studies [85,86] are confirmed, it is reasonable to imagine that there are still about 4 to 5 years before the complete loss of the cultural landscape of this large portion of the Nile valley due to the progressive dam filling process.…”
Section: Grand Ethiopian Renaissance Dam (Gerd)mentioning
confidence: 99%
“…However, due to the influence of climate change, ensuring the consistency and reliability of power supply has become one of the most pressing issues [ 21 ]. On the other hand, the majority of reservoirs in Ethiopia are designed, maintained, and operated under the assumption of stationary historical climate data [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies are done that showed the likely impact of climate change on the hydropower potential and hydroelectricity generation of Ethiopia. For instance, Bombelli et al [ 21 ] investigated the impact of climate change on the hydroelectric power generating capacity of GERD and GIBE reservoirs. To simulate the ideal power production and the future hydrological balance, they used Poli-Hydro and Poli-Power models.…”
Section: Introductionmentioning
confidence: 99%